Impact of phosphamidon on total protein, carbohydrate and lipid contents during the larval development of Sesarma brockii de Man - Kannupandi, T; Vijayakumar, G; Soundarapandian, P (Indian Journal of Fisheries, 2011)
Exposing the four zoeal and megalopal stage of the mangrove crab Searma borckii to different concentrations of phosphamidon, the larval survivability and the biochemical constituents such as protein, carbohydrate and lipid were studied. In all three test concentrations (0.025,1.108 and 1.600 ng/1) studied, a reduction in survival rate, prolonged intermoult duration and decrease of total protein, carbohydrate and lipid contents was observed. The result was subjected to ’F’ test and multiple range test to know their statistical significance